2020
DOI: 10.1002/ece3.6185
|View full text |Cite
|
Sign up to set email alerts
|

Panmixia across elevation in thermally sensitive Andean dung beetles

Abstract: Janzen's seasonality hypothesis predicts that organisms inhabiting environments with limited climatic variability will evolve a reduced thermal tolerance breadth compared with organisms experiencing greater climatic variability. In turn, narrow tolerance breadth may select against dispersal across strong temperature gradients, such as those found across elevation. This can result in narrow elevational ranges and generate a pattern of isolation by environment or neutral genetic differentiation correlated with e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Populations in the H. leucophrys complex occurring at high elevations in the Sierra Nevada de Santa Marta (Caro et al, 2013) and the Andes of Ecuador (Dingle et al, 2008(Dingle et al, , 2010 Marta and the Andes, regional differences in factors other than, or in addition to temperature, have led to an absence of convergent evolution in feathers; or (3) populations from different regions may have responded to the challenges of high elevations in different ways (e.g., more insulative plumage vs. greater thermogenic capacity). Alternatively, we speculate that in mountains where a single species exists across a large elevational gradient, high gene flow along mountain slopes (as shown in Linck et al, 2020and Pujolar et al, 2022, but see Polato et al, 2018 may restrict the emergence of adaptive variation in the highlands owing to swamping of locally beneficial alleles by maladaptive variants arriving via dispersal from lower elevations (Bachmann et al, 2020;Bridle et al, 2009;Bridle & Vines, 2007;Polechová & Barton, 2015). In…”
Section: Discussionmentioning
confidence: 85%
“…Populations in the H. leucophrys complex occurring at high elevations in the Sierra Nevada de Santa Marta (Caro et al, 2013) and the Andes of Ecuador (Dingle et al, 2008(Dingle et al, , 2010 Marta and the Andes, regional differences in factors other than, or in addition to temperature, have led to an absence of convergent evolution in feathers; or (3) populations from different regions may have responded to the challenges of high elevations in different ways (e.g., more insulative plumage vs. greater thermogenic capacity). Alternatively, we speculate that in mountains where a single species exists across a large elevational gradient, high gene flow along mountain slopes (as shown in Linck et al, 2020and Pujolar et al, 2022, but see Polato et al, 2018 may restrict the emergence of adaptive variation in the highlands owing to swamping of locally beneficial alleles by maladaptive variants arriving via dispersal from lower elevations (Bachmann et al, 2020;Bridle et al, 2009;Bridle & Vines, 2007;Polechová & Barton, 2015). In…”
Section: Discussionmentioning
confidence: 85%
“…High rates of gene flow have been observed in other arthropods. For example, a study of five Andean dung beetle species found panmixia (Linck et al, 2020), which may be in part due to the use of a common resource of dung that becomes a point of gene flow between different populations of each species when the dung is visited at the same point in time. At CRMO, the kipukas may be acting as a common resource for M. celer as they contain abundant vegetation and common habitat for copulation.…”
Section: Discussionmentioning
confidence: 99%
“…The species that occur at low and high elevations in tropical biomes often have large differences in their climatic tolerances compared to those inhabiting temperate areas (Janzen 1967; Linck et al . 2020). Hence, the differences in the environmental characteristics of the occurrences as suggested by the use of coarse‐grain geographical data are congruent with the patterns recognized at fine‐grain local scale (Hensen et al .…”
Section: Discussionmentioning
confidence: 99%